Epidemiology of Traumatic Cervical Spinal Cord Injury in Southeast Norway - Mona Strøm; Jalal Mirzamohammadi; Thomas Glott; Tor Brommeland; Hege Linnerud; Pål Andre Rønning; Syed Ali Mujtaba Rizvi; Donata Biernat; Tor Arnøy Austad; Marianne Efskind Harr; Mads Aarhus; Eirik Helseth (Neurotrauma Reports)
A traumatic cervical spinal cord injury (cSCI) is a severe consequence of trauma to the cervical spine with high mortality and morbidity rates. Epidemiological studies of traumatic cSCIs are necessary for planning preventive measures and health care resource allocation. This is a retrospective database study of 387 consecutive patients with traumatic cSCI admitted to hospitals in Southeast Norway between 2015 and 2022. The estimated incidence of traumatic cSCI was 1.6 per 100,000 per year. The incidence rates adjusted for standard European and global populations were 1.7 and 1.1 per 100,000 per year, respectively. The median patient age was 64 years, 75% were males, 40% had severe comorbidities, 65% of injuries were caused by falls, 25% were ethanol influenced, 44% had multiple traumas, and 96% were admitted to the Neurotrauma Center (NTC). In patients with C0–C2 injury, an odontoid fracture with dislocation of the odontoid fragment was most frequent. The most frequent subaxial injuries were, according to the AO Spine subaxial cervical spine injury classification system, minor nonstructural injuries (type A0) and translational injuries (type C). Eleven percent of patients were diagnosed with cSCIs at C0–C2, and 89% of cSCIs were subaxial. According to the American Spinal Injury Association (ASIA) Impairment Scale (AIS), 17% of cSCIs were classified as A, 12% B, 24% C, and 47% D. Forty-three percent of patients were classified as central cord syndrome, which was significantly associated with subaxial injuries and preinjury degenerative cervical spinal stenosis. Compromised respiration due to the cSCI itself was diagnosed in 17% of patients and was predominant in patients with complete cSCIs (AIS A or B) and high cervical injuries. These data will be helpful in planning the capacity of NTCs in the future. Interventions to prevent falls in elderly individuals and to increase awareness of ethanol as a risk factor for severe cSCIs are needed.